THE CRITICAL ROLE OF CYBERSECURITY IN PRIVACY PROTECTION: A TECHNICAL PERSPECTIVE - Ganesh Marrivada, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
As businesses deal with more complex challenges, the integration of cybersecurity and privacy protection has become critical in today's digital environment. This in-depth study examines the development of privacy protection technologies, looking at important topics such as real-time threat detection systems, authentication methods, and encryption protocols. The application of Privacy-Enhancing Technologies (PETs), sector-specific privacy solutions in the banking and healthcare industries, and cutting-edge technologies like quantum-safe encryption are all examined in this article. This article shows how businesses modify their security architectures to handle contemporary privacy issues while preserving operational effectiveness by looking at existing frameworks and emerging trends. The essay offers insights into the real-world application of privacy protection tactics in a variety of industries by combining cutting-edge technologies with conventional security measures.